EFFECTIVENESS STUDIES OF THE LEARNING BASIC MATHEMATICAL OPERATIONS ON USERS USING EDUCATION GAMES WITH ESCALATING DIFFICULTY LEVEL IN SEVERAL TYPES OF GAMES - Ari Mahardika Ahmad Nafis; Darlis Herumurti (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2020)
Mathematic is basic but fundamental knowledge, but in fact many students do not have the motivation to learn it because they think mathematic is boring. Therefore, an innovation is needed to motivate students, one of them is by using an educational game. Racing, shooting and fighting games are the most popular types of games in 2019 according to InvisionCommunity. Shooting game is a genre that used a lot in the educational games for learning math, while racing game and fighting game are not used much for educational games. This research aims to develop and measure the effectiveness of the games from these three genre of games as a means of learning elementary arithmetic at the elementary school level. The effectiveness of an educational game can be observed from the increment in learning outcomes obtained after conducting an experiment. We can know the most effective type of game in this experiment by compare the improvement in learning outcomes after playing all three games. The comparative analysis will be carried out using ANOVA. In this research, we used data from 60 participant with elementary level of education between grade 1 to 3. The results were obtained by calculating the difference in the participants' initial scores obtained from before playing the game and participants’ final scores obtained after playing the educational game. The results show that educational racing games have the highest increase of 6.3% compared to shooter games with 3% increase or fighting games with increase of 4.3%.